(untitled) (Journal of Comparative & International Higher Education, 2024)
Aprender en Comunidad: Prácticas Colaborativas para Transformar la Evaluación (Learning in Community: Collaborative Practices to transform Assessment) is the joint creation of Argentinian and Uruguayan practitioners. As much of the current discourse in comparative and international higher education is on the Global North, this book expands the discussion to territories historically excluded from the conversation. The book has a prologue by a university lecturer and researcher and is structured in seven chapters, which go from telling about the constitution of the work team, through the statement of their common goal: the design of improved course planning with authentic assessment tasks, to the reflection on the implementation of such proposals, as well as on the experiential knowledge gained from the collaborative work within the community of learning. The book’s purpose is then to describe and reflect upon those proposals with the intention of inspiring similar collaborative assessment practices. While the book is written in Spanish, the intended audience is any teacher, teacher trainer/trainee, college/university educator or tertiary level student who wants to read about varied innovative assessment experiences, carried out mainly at higher education (HE) institutions, and the synergy that learning from and with other colleagues harnesses.